Education on zero water discharge technology based on solar panels in vaname shrimp cultivation at Bustan Assofa Islamic Boarding School, Banda Aceh City [Edukasi teknologi zero water discharge berbasis solar panel dalam budidaya udang vaname di Pesantren Bustan Assofa Kota Banda Aceh] - Putra, Dedi Fazriansyah; Wahab, Gunawan Abdul; Jalil, Zulkarnaen (Universitas Syiah Kuala, 2025)
The Zero Water Discharge (ZWD) technology is highly effective for efficient water usage, reducing or even eliminating wastewater discharge typically associated with shrimp farming. Used water from shrimp ponds can be treated and recycled, preventing any liquid waste from being released into the environment. By utilizing energy generated from solar panels (SP), this shrimp farming practice becomes more environmentally friendly and sustainable. Renewable natural resources, specifically sunlight, are harnessed to operate the system without increasing the carbon footprint. The objective of this initiative is to transfer the appropriate ZWD technology based on SP in shrimp farming to the community of Gampong Alue Naga, particularly Dayah Bustan Assofa. The implementation method began with the initial observation by the team of volunteers of the shrimp farming practices in the dayah, which often faced various challenges, such as foul-smelling pond water due to poor water quality. Additionally, high electricity costs also hindered shrimp farming in the dayah. To address these issues, ZWD technology based on SP was applied. The results of the initiative indicate that the implementation of SP-based ZWD technology in vaname shrimp farming in Banda Aceh proceeded as planned, without encountering any significant obstacles in the field. The partners were very supportive and enthusiastic, requesting that their area be designated as a mentoring village by FKP USK. Future recommendations include enhancing capacity in marketing, particularly digital marketing, which is beneficial for expanding the market reach of farmers, enabling them to sell their products to a wider consumer base at better prices.